Integrated morphological, proteomic and metabolomic analyses reveal response mechanisms of microalgae under uranium exposure - Han, Mengwei; Yang, Xu; Dong, Bin; Lai, Jinlong; Xi, Hailing; Zhao, Sanping (Frontiers in Microbiology, 2025)
IntroductionThe release of uranium (U)-containing wastewater poses a significant threat to aquatic ecosystems. However, the response mechanisms of microalgae to U stress remain poorly understood.MethodsThis study employed an integrated approach, combining morphological, physiological, proteomic, and metabolomic analyses, to investigate the tolerance and accumulation mechanisms of the microalga Ulothrix sp. under a gradient of U exposure (40 to 400 μmol/L).ResultsUlothrix sp. exhibited a dose-dependent U accumulation, reaching up to 2,100 mg/kg dry weight, which competitively inhibited the uptake of phosphorus and zinc. Physiologically, medium and high U concentrations reduced chlorophyll *a* content by 49–65% and significantly impaired photosystem II efficiency (Fv/Fm), while increasing energy dissipation (DIo/RC) by 1.82–2.01 times. Antioxidant defense responses were activated, with significant upregulation of superoxide dismutase (SOD) and catalase (CAT) activities (p < 0.05), a 2.2-fold increase in oxidized glutathione (GSSG), and inhibition of peroxidase (POD) activity. Proteomic analysis revealed that differentially expressed proteins (DEPs) were predominantly enriched in pathways related to carbohydrate metabolism and transport. Concurrently, metabolomic profiling indicated a specific activation of the glycine-serine-threonine pathway and a significant enrichment in glycerophospholipid metabolism (ko00564).DiscussionOur findings demonstrate that Ulothrix sp. mitigates U-induced stress and maintains cellular homeostasis through a multi-level defense network. This network encompasses the activation of antioxidant enzymes, remodeling of key tricarboxylic acid (TCA) cycle metabolites, and strategic regulation of the glycine-serine-threonine metabolic pathway. This study provides crucial insights into the molecular and physiological basis of U tolerance in microalgae.